Five Walls and a Roof - Dale A. Bryant (Oz, 1988)
Ever so long ago before anything was modern, O Best Beloved, each house had just four walls and a roof. They were plain boxes with simple gables that glanced against the great blue cloud-scudded sky and there were no interfaces, interferences, or international styles to stumble on to...